THE PROCESS OF CULTURAL ADAPTATION AMONG STUDENTS PARTICIPATING IN INTERNATIONAL EXCHANGE PROGRAMS: STUDY AND ANALYSIS - Allayarova, Zebiniso; Jalilova, Nilufar (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
The rapid expansion of international exchange programs has increased the importance of understanding students’ cultural adaptation to new academic and social environments. Cultural adaptation significantly influences exchange students’ academic success, psychological well-being, and intercultural competence. This article provides a systematic literature review of research on cultural adaptation processes among students participating in international exchange programs. Based on key theoretical frameworks such as acculturation theory, culture shock theory, and intercultural communication models, the review synthesizes findings from studies conducted in diverse educational contexts. The analysis highlights major factors affecting adaptation, including acculturation strategies, language self-confidence, social integration, and institutional support. The article concludes by emphasizing the joint role of students and host institutions in facilitating successful cultural adaptation.